(untitled) (Physical Education, Health and Social Sciences, 2026)
This study examine the influence of aggressive mobile games on the psychological, behavioral and academic performances of teenagers in District Sargodha, Punjab, Pakistan. As smartphone usage and digital gaming among the youth are rapidly growing, the increase adverse implications of aggressive gaming on the mental wellbeing and social conduct of the teenagers has become a growing concern. The main aim of the study was to explore the impact of exposure to aggressive mobile games on the psychological health, behavioral habits, tendencies toward addictions, and educational achievements of teenagers. The quantitative research design used and the survey method of data collection was cross-sectional based on which teenagers aged 14-18 years living in the District Sargodha. There are 382 respondents were chosen using a convenience sampling method in different schools. A structured questionnaire of demographic data and statements that quantified gaming exposure and its psychological and behavioral effects were used to collect data. The answers were registered on a five point Likert level that included strongly disagree to strongly agree. The Cronbachs Alpha was used to test the reliability and internal consistency of the data. The data was analyzed with the help of SPSS with the application of descriptive and inferential statistics. Demographic characteristics and response patterns were summarized by descriptive statistics like frequencies, percentages, means, and standard deviations. Inferential tests involved Independent Samples t-test, Two-Way ANNOVA, Pearson correlation and Multiple regression analysis to check the relationship and predictive impact among variables. The findings showed that there were strong associations between exposure to aggressive gaming and psychological influence among teenagers. Regression analysis showed that the exposure to games, addiction dependency, and behavioral outcomes are important predictors of psychological outcomes, with the gaming exposure effect being the strongest. The results indicate that overexposure to violent mobile games can lead to higher levels of psychological stress, behavioral disorders, and addiction among young people that affect their learning and social life as well. The results indicates the importance of parental surveillance, education and awareness campaigns to help teenagers to embrace balanced and responsible gaming behaviors.